2020
DOI: 10.3892/ol.2020.11423
|View full text |Cite
|
Sign up to set email alerts
|

Early risk warning system for distant metastasis of hepatitis B virus‑associated hepatocellular carcinoma with portal vein tumor thrombus

Abstract: Portal vein tumor thrombus (PVTT) promotes distant metastasis of hepatocellular carcinoma (HCC), which increases the mortality of patients with HCC and PVTT. The aim of the present study was to develop an early risk warning system for distant metastasis of hepatitis B virus (HBV)-associated primary HCC (HBV-HCC) with PVTT. Data from 346 patients (263 and 83 in the modeling and validation cohorts, respectively) who had received primary diagnoses of HBV-HCC and PVTT between January 2012 and June 2015 at Beijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Firstly, previous studies found that patients with portal vein tumor thrombosis (PVTT) usually decreased liver function reserves, which was a high-risk factor for disease progression and recurrence ( 29 , 30 ). In addition to tumor thrombus, tumor volume is also associated with HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, previous studies found that patients with portal vein tumor thrombosis (PVTT) usually decreased liver function reserves, which was a high-risk factor for disease progression and recurrence ( 29 , 30 ). In addition to tumor thrombus, tumor volume is also associated with HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In addition, patients with PVTT who did not develop distant tumor metastases were more likely to exhibit thrombocytopenia than those who did. 38 In the reverse direction, a major study of the Lancet concluded that antiplatelet therapy could inhibit tumor metastasis and improve patient prognosis, but the survival rate of the low-concentration drug group was significantly higher than that of the high-concentration group. 39 These support our findings that thrombocytopenia may be an important prognostic factor in patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 It has been reported that AST levels ≥118.5 U/L are significantly associated with distant metastasis of primary HCC with portal vein tumour thrombus (PVTT). 34 An AST level of ≥2× the upper limit of normal (ULN) is an independent indicator for poor prognosis. 35 These studies demonstrated that elevated AST levels are closely related to the prognosis of HCC and are an independent risk factor for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%